Insect Vectors of Disease: Untapped Reservoirs for New Antimicrobials? - Tobias, Nicholas J. (Frontiers in Microbiology, 2016)
With the increase in antibiotic resistance among infectious diseases, the need for new strategies for identifying compounds with inhibitory effects is dire. Traditional methods of genome sequencing and systematic characterization of potential antimicrobial gene clusters, although effective, are unfortunately not yielding results at a speed consistent with the rise in antimicrobial resistance. One approach could be to use a more targeted approach to antimicrobial compound discovery. Insect vectors often mediate the transmissions of parasitic infections for example, leishmaniasis, malaria and trypanosomiasis. Within the insect, among the pathogens, are commensal and/or obligate symbiotic bacteria, which often undergo a population shift upon colonization of the insect host. The remaining bacteria may be either resistant to the effects of the respective parasites, or possibly essential for a successful colonization and continued spread of the parasite due to an obligate symbiosis between bacteria and insect host. Interestingly, these shifts are often towards groups of bacteria known to harbor many polyketide synthase and non-ribosomal peptide synthetase gene clusters involved in bioactive molecule production. This perspective explores the possibility to exploit the natural interactions between parasite, symbiont and insect host for a more targeted approach towards natural product discovery, in an environment where potential compound producers are naturally interfacing with human pathogens.